A Novel Cellular Therapy to Treat Pancreatic Pain in Experimental Chronic Pancreatitis Using Human Alpha-1 Antitrypsin Overexpressing Mesenchymal Stromal Cells - Rebecca P. Chow; Kevin Nguyen; Wenyu Gou; Erica Green; Katherine Morgan; William Lancaster; Kristi Helke; Charlie Strange; Hongjun Wang (Biomedicines, 2021)
Chronic pancreatitis (CP) is characterized by pancreatic inflammation, fibrosis, and abdominal pain that is challenging to treat. Mesenchymal stromal cells (MSCs) overexpressing human alpha-1 antitrypsin (hAAT-MSCs) showed improved mobility and protective functions over native MSCs in nonobese diabetic mice. We investigated whether hAAT-MSCs could mitigate CP and its associated pain using trinitrobenzene sulfonic acid (TNBS)-induced CP mouse models. CP mice were given native human MSCs or hAAT-MSCs (0.5 × 106 cells/mouse, i.v., n = 6–8/group). The index of visceral pain was measured by graduated von Frey filaments. Pancreatic morphology and pancreatic mast cell count were analyzed by morphological stains. Nociceptor transient receptor potential vanilloid 1 (TRPV1) expression in dorsal root ganglia (DRG) was determined by immunohistochemistry. hAAT-MSC-treated CP mice best preserved pancreatic morphology and histology. MSC or hAAT-MSC infusion reduced abdominal pain sensitivities. hAAT-MSC therapy also suppressed TRPV1 expression in DRG and reduced pancreatic mast cell density induced by TNBS. Overall, hAAT-MSCs reduced pain and mitigated pancreatic inflammation in CP equal to MSCs with a trend toward a higher pancreatic weight and better pain relief in the hAAT-MSC group compared to the MSC group. Both MSCs and hAAT-MSCs might be used as a novel therapeutic tool for CP-related pain.